Supra-Optimal Temperature: An Efficient Approach for Overaccumulation of Starch in the Green Alga Parachlorella kessleri - Vilém Zachleder; Veronika Kselíková; Ivan N. Ivanov; Vitali Bialevich; Milada Vítová; Shuhei Ota; Tsuyoshi Takeshita; Shigeyuki Kawano; Kateřina Bišová (Cells, 2021)
Green algae are fast-growing microorganisms that are considered promising for the production of starch and neutral lipids, and the chlorococcal green alga Parachlorella kessleri is a favorable model, as it can produce both starch and neutral lipids. P. kessleri commonly divides into more than two daughter cells by a specific mechanism—multiple fission. Here, we used synchronized cultures of the alga to study the effects of supra-optimal temperature. Synchronized cultures were grown at optimal (30 °C) and supra-optimal (40 °C) temperatures and incident light intensities of 110 and 500 μmol photons m−2 s−1. The time course of cell reproduction (DNA replication, cellular division), growth (total RNA, protein, cell dry matter, cell size), and synthesis of energy reserves (net starch, neutral lipid) was studied. At 40 °C, cell reproduction was arrested, but growth and accumulation of energy reserves continued; this led to the production of giant cells enriched in protein, starch, and neutral lipids. Furthermore, we examined whether the increased temperature could alleviate the effects of deuterated water on Parachlorella kessleri growth and division; results show that supra-optimal temperature can be used in algal biotechnology for the production of protein, (deuterated) starch, and neutral lipids.